MAPPING THE LANDSCAPE OF EXPLORATORY READING: A BIBLIOMETRIC ANALYSIS - Yusup, Rahmad; Ismail, Hijril; Rahmaniah, Rima (English Review: Journal of English Education, 2025)
The exploration of reading is pivotal for enhancing comprehension, fluency, and critical thinking. Despite its importance, discrepancies persist between theoretical models and practical applications in reading education. The objective of this study is to present a thorough review of the literature on exploring reading. Articles were searched using Publish or Perish with Scopus Database. The study analyzed 147 articles from 2019-2023. The Mendeley software is utilized to resume and manage references. The researchers applied to VOSviewer to review and identify articles. Seven clusters have been identified. Cluster 1 is comprised of seven items: academic vocabulary, influence, older adult, performance, reading comprehension, relationships, and self. Cluster 2 consisted 7 item: academic performance, children, online reading, poor reading comprehension, primary school student, research, and strategy. Cluster 3 consists of five items: college student, effectiveness, experience, feedback, and type. Cluster 4 consists of 5 items: achievement, adult, context, effect, and reading. Cluster 5 consists of 4 items: elt reading comprehension, factors, impact, and practice. Cluster 6 consisted of 4 items: adult reader, theory, vocabulary, and word reading. Cluster 7 consisted 3 item. Connections, knowledge, and roles.